ByzRev 07.2025.009: Jason Fossella, The dromos and Byzantine communications, diplomacy, and bureaucracy, 518–1204: (The Medieval Mediterranean 137). Leiden – Boston: Brill 2023. - McMahon, Lucas (The Byzantine Review, 2025)
Jason Fossella, The dromos and Byzantine communications, diplomacy, and bureaucracy, 518–1204 (The Medieval Mediterranean 137). Leiden – Boston: Brill 2023. XV, 202 pp. – ISBN 978-90-04-68127-9